Oral Immunization of Larvae and Juvenile of Lumpfish (Cyclopterus lumpus) against Vibrio anguillarum Does Not Influence Systemic Immunity - My Dang; Trung Cao; Ignacio Vasquez; Ahmed Hossain; Hajarooba Gnanagobal; Surendra Kumar; Jennifer R. Hall; Jennifer Monk; Danny Boyce; Jillian Westcott; Javier Santander (Vaccines, 2021)
Vibrio anguillarum, a marine bacterial pathogen that causes vibriosis, is a recurrent pathogen of lumpfish (Cyclopterus lumpus). Lumpfish is utilized as a cleaner fish in the Atlantic salmon (Salmo salar) aquaculture in the North Atlantic region because of its ability to visualize and prey on the ectoparasite sea lice (Lepeophtheirus salmonis) on the skin of Atlantic salmon, and its performance in cold environments. Lumpfish immunity is critical for optimal performance and sea lice removal. Oral vaccine delivery at a young age is the desired method for fish immunization because is easy to use, reduces fish stress during immunization, and can be applied on a large scale while the fish are at a young age. However, the efficacy of orally delivered inactivated vaccines is controversial. In this study, we evaluated the effectiveness of a V. anguillarum bacterin orally delivered to cultured lumpfish and contrasted it to an intraperitoneal (i.p.) boost delivery. We bio-encapsulated V. anguillarum bacterin in Artemia salina live-feed and orally immunized lumpfish larvae. Vaccine intake and immune response were evaluated by microscopy and quantitative polymerase chain reaction (qPCR) analysis, respectively. qPCR analyses showed that the oral immunization of lumpfish larvae resulted in a subtle stimulation of canonical immune transcripts such as il8b, il10, igha, ighmc, ighb, ccl19, ccl20, cd8a, cd74, ifng, and lgp2. Nine months after oral immunization, one group was orally boosted, and a second group was both orally and i.p. boosted. Two months after boost immunization, lumpfish were challenged with V. anguillarum (7.8 × 105 CFU dose−1). Orally boosted fish showed a relative percentage of survival (RPS) of 2%. In contrast, the oral and i.p. boosted group showed a RPS of 75.5% (p < 0.0001). V. anguillarum bacterin that had been orally delivered was not effective in lumpfish, which is in contrast to the i.p. delivered bacterin that protected the lumpfish against vibriosis. This suggests that orally administered V. ...